2022
DOI: 10.3390/su14159571
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin from Lacticaseibacillus rhamnosus sp. A5: Isolation, Purification, Characterization, and Antibacterial Evaluation for Sustainable Food Processing

Abstract: A new Lacticaseibacillus rhamnosus strain A5 was isolated from pickle soup and characterized for its probiotic suitability. Strain A5 was Gram-positive, catalase-negative, acid-producing, and exhibited potential antibacterial activity against Escherichia coli (inhibition zone 17.3 mm), Bacillus subtilis (inhibition zone 14.5 mm), Salmonella enterica (zone of inhibition 16.1 mm) and Staphylococcus aureus (zone of inhibition 14.2 mm) by performing investigations on the disc diffusion. The cell-free supernatant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1a. The absorption peaks at 228 nm and 280 nm in the UV spectrum indicated that the crude extracts consisted of proteins and peptides (Liao et al ., 2017; Biter et al ., 2019), which indicated that crude extracts might be bacteriocin (Ren et al ., 2022). A previous study also indicated that bacteriocins were antimicrobial proteins or peptides produced by lactic acid bacteria that had the potential to combat contamination by pathogenic bacteria in food (Garsa et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…1a. The absorption peaks at 228 nm and 280 nm in the UV spectrum indicated that the crude extracts consisted of proteins and peptides (Liao et al ., 2017; Biter et al ., 2019), which indicated that crude extracts might be bacteriocin (Ren et al ., 2022). A previous study also indicated that bacteriocins were antimicrobial proteins or peptides produced by lactic acid bacteria that had the potential to combat contamination by pathogenic bacteria in food (Garsa et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…After incubation at each point, the supernatant (1 mL) was collected, and the bacterium released was determined using the pour plate technique in MRS agar. The index of cell release was calculated by equation (3).…”
Section: Release Performancesmentioning
confidence: 99%
“…Recently, the name L. paracasei was changed to Lacticaseibacillus paracasei because the genome diverged from Lactobacillus [2]. It has been demonstrated that bacteria in the genus Lacticaseibacillus are capable of creating bacteriocins, antimicrobial peptides utilized in the food and healthcare industries [3,4]. Unfortunately, factors in the gastrointestinal tract such as low pH, low enzyme levels, and low bile salts make it difficult for free probiotic cells to survive in the body after oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that more than half of almost all bacterial species can produce bacteriocins [66]. In this regard, Ren et al [67] reported the noticeable antibacterial activity of L. rhamnosus sp. A5 against E. coli, B. subtilis, Salmonella, and S. aureus.…”
Section: Bio-preservation Of Fermented Meat Products By Starter Labmentioning
confidence: 99%